Variations in the Root Form and Root Canal Morphology of Permanent Mandibular canine - Shrestha, Kriti; Shubham, Snigdha; Ahmed, Sageer; Gautam, Vanita (Journal of Nepal Health Research Council, 2024)
Background: Mandibular canines are recognized as usually having one root and one root canal in most cases. However, many investigators have reported the anatomical variations associated with mandibular canines. Thus; the objective of this study is to determine the number of roots and morphology of the root canal system of permanent mandibular canine in a Nepalese population. Methods: Cone Beam Computerized Tomography images of 390 patients in a Nepalese population were selected, and a total of 780 mandibular canines were analyzed. The number of root and the canal configurations were investigated. Data were analyzed with descriptive analysis and Chi-square tests using the Statistical Package for the Social Sciences (SPSS) software version 20 (SPSS Inc, Chicago, IL, USA). Results: Out of the 780 mandibular canines, 741(95%) were single-rooted canines while only 39 (5%) were double-rooted canines. The most common type of Vertucci in single-rooted canines was Type I (1-1) in the percentage of 85.6% and the least type was Type IV (1-2) in the percentage of (2.5%). The Chi-square tests showed no significant association between gender and number of roots (P = 0.87) and gender and root canal configuration in single-rooted canine (P = 0.52). Conclusions: All mandibular permanent canines were single rooted but 5.2% of the permanent mandibular canines had two roots. Keywords: Canine; Cone Beam Computerized Tomography (CBCT); double root; root canals.